Rural development and rural tourism in the municipality of Petrovac na Mlavi - Vedrana Babić; Radovan Lala Davidov; Marko Jovanović (Ekonomika Poljoprivrede (1979), 2018)
Community Petrovac na Mlavi is located in Eastern Serbia, in county Branicevo. His spread 654. 9 km². By the census in this community lives 45 706 inhabitants (Serbian and Vlahian origin). City Petrovac as the center of community has 8 772 inhabitant Relief is represented with hills and plains. Climate is moderate continental. Hidrography is represented by river Mlava with her fributeries. Tis community is tich with different animal and herbal species.